Biogenic Manganese‐Oxide Mineralization is Enhanced by an Oxidative Priming Mechanism for the Multi‐Copper Oxidase, MnxEFG. Issue 6 (21st December 2016) - Tao, Lizhi; Simonov, Alexandr N.; Romano, Christine A.; Butterfield, Cristina N.; Fekete, Monika; Tebo, Bradley M.; Bond, Alan M.; Spiccia, Leone; Martin, Lisandra L.; Casey, William H.
Abstract: In a natural geochemical cycle, manganese‐oxide minerals (MnO x ) are principally formed through a microbial process, where a putative multicopper oxidase MnxG plays an essential role. Recent success in isolating the approximately 230 kDa, enzymatically active MnxEFG protein complex, has advanced our understanding of biogenic MnO x mineralization. Here, the kinetics of MnO x formation catalyzed by MnxEFG are examined using a quartz crystal microbalance (QCM), and the first electrochemical characterization of the MnxEFG complex is reported using Fourier transformed alternating current voltammetry. The voltammetric studies undertaken using near‐neutral solutions (pH 7.8) establish the apparent reversible potentials for the Type 2 Cu sites in MnxEFG immobilized on a carboxy‐terminated monolayer to be in the range 0.36–0.40 V versus a normal hydrogen electrode. Oxidative priming of the MnxEFG protein complex substantially enhances the enzymatic activity, as found by in situ electrochemical QCM analysis. The biogeochemical significance of this enzyme is clear, although the role of an oxidative priming of catalytic activity might be either an evolutionary advantage or an ancient relic of primordial existence. Abstract : In a natural geochemical cycle, manganese‐oxide minerals (MnO x ) are principally formed through a diurnal microbial process, where a putative multicopper oxidase MnxG plays an essential role. Here, the kinetics of MnO x formation catalyzed by MnxEFG are examined using a quartz crystal microbalance, and the first electrochemical characterization of the MnxEFG complex is reported using Fourier‐transformed alternating current voltammetry.